Dieulafoy Lesion in the Stomach - A. Isik; O. Alimoglu; I. Okan; G. Bas; H. Turgut; M. Sahin (Case Reports in Gastroenterology, 2008)
Dieulafoy disease is an uncommon cause of gastrointestinal system bleeding. Although the exact cause is not known, it is characterized by bleeding from abnormal submucosal vessels. There are many methods for diagnosis and treatment. In this case, a patient with a long-time undiagnosed stomach Dieulafoy lesion had a surgical resection. During the postoperative period the patient was discharged without any complication.